2015
DOI: 10.1111/cei.12558
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of portal hepatic infiltrating leucocytes in acute drug-induced liver injury, idiopathic autoimmune and viral hepatitis

Abstract: + T cells and macrophages. DILI cases had significantly fewer B lymphocytes than AIH and VH and significantly fewer NK cells than VH. Prominent plasma cells were unusual in IAD (three of 10 cases), but were associated strongly with AIH (eight of nine) and also observed in most with AID (six of nine). They were also found in five of 10 cases with VH. Liver biopsies from subjects with DILI were characterized by low counts of mature B cells and NK cells in portal triads in contrast to VH. NK cells were found only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 28 publications
(29 reference statements)
3
71
0
3
Order By: Relevance
“…The prominent histological features indicated above are also present in many other acute or chronic liver diseases 60 63 74 75. However, when occurring in combination, they may favour a diagnosis of AIH.…”
Section: Discussionmentioning
confidence: 92%
“…The prominent histological features indicated above are also present in many other acute or chronic liver diseases 60 63 74 75. However, when occurring in combination, they may favour a diagnosis of AIH.…”
Section: Discussionmentioning
confidence: 92%
“…In recent work from DILIN, we have shown that AC and other agents associated with immuno-allergic injury cause hepatitis with infiltration of portal triads by many T cells, most of which are CD8+ cytotoxic T cells [19]. These and other findings suggest that the pathogenesis of the liver injury is primarily an immune-mediated attack on cholangiocytes or perhaps on the apical pole of hepatocytes.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, studies of lymphocyte subsets in liver tissue samples have demonstrated that DILI subjects are less likely to have Natural killer cells, CD4+ T-Helper, and B-cells compared to patients with acute viral hepatitis (61). The predominance of CD8 + cytotoxic T-cells in the livers of idiosyncratic DILI patients is consistent with the hypothesis that the intrahepatic generation of neo-antigens from the drug or its metabolite may lead to the recruitment and activation of T-lymphocytes that can initiate or perpetuate the liver injury (62).…”
Section: Inferences Of Dili Pathogenesis From Liver Histologymentioning
confidence: 99%